ASEAN COMISSION ON PROMOTION AND PROTECTION OF RIGHTS OF WOMEN AND CHILDREN ( ACWC ) POLICIES IN ME VIOLENCE RESPONSE TO WOMEN IN THE SPIRIT - Rini Afriantari; M Budiana (Lembaga Penelitian Universitas Pasundan, 2020)
The conflict in Rohingnya is not a new thing for countries in the Southeast Asia region, this conflict has been going on for along time and is one form of gross human rights violatins. Many of the Rohingnya people who accept physical and psychological violence are no exception for women, women in the Rohingnya not only accept ordinary physical violence but also accept sexual violence as well. This study aims to explain why ACWC seems helpless in dealing with violence against women that occurs in the Rohingnya.